Why East Asian Objects in Slovenia Became “Orphaned” - Nataša Vampelj Suhadolnik (Asian Studies)
What lies behind the impoverishment of the identity of East Asian objects in their transition from the private to the public sphere? This article looks at the various developmental processes that have led to the “orphaning” of East Asian objects in Slovenia and discusses the challenges of provenance research for such objects, proposing a new research approach. Objects of East Asian origin became “orphaned” in various ways, either being sold by aristocrats, confiscated by Nazi occupying forces or the socialist government institutions during or after WWII, or given or sold to persons who did not preserve their history. All processes were poorly documented and only sparse notes were made. This makes it extremely difficult for researchers to trace the biographies of these objects and identify their past ownership. Many other records, such as photographs of interiors and other object documents, have also been lost due to the complex socio-political situation and the mobility of the objects between the private and public spheres.